'Growth oriented' corporate governance reform – can it solve Japan's performance puzzle?. Issue 3 (3rd July 2017) - Waldenberger, Franz
Abstract: Recent governance reforms in Japan aim at promoting 'the establishment of an environment that supports appropriate risk-taking by the senior management.' The article evaluates the reforms on the basis of two questions: do the reforms tackle the right issues? And will they be effective? The Japanese economy faces indeed a performance puzzle. Despite Japan's strong efforts in the field of research and development, its excellent work force and abundant financial capital, the economy is performing poorly in terms of productivity. The performance puzzle seems to be closely related to the way large Japanese companies are governed, namely by boards filled with internally promoted lifetime employees. However, the correlation between board composition and performance is spurious. Both are influenced by a third factor, which manifests itself in the predominance of in-house careers. In-house careers determine the composition of boards and have, over the last twenty years, had a negative impact on economic performance. The governance reforms do not address the root of Japan's performance puzzle. They may nevertheless provide an important stimulus for redesigning the way Japanese corporations recruit, train and promote future leaders.